Management of achilles tendon injury - Che Ahmad, Aminudin (Malaysian Orthopaedic Association, 2012)
Achilles tendon injury is a common cause of disability in adult sportsmen. The majority of cases are due to overuse injury often exacerbated or precipitated by specific and recognizable factors. The main reason is probably the increased popularity of recreational sports among middle-aged people. The 2 most frequently discussed pathophysiological theories involve chronic degeneration of the tendon and failure of the inhibitory mechanism of the musculotendinous unit. It has been postulated that a physically inactive lifestyle leads to a decrease in tendon vascularization, while maintenance of a continuous level of activity counteracts the structural changes within the musculotendinous unit induced by inactivity and aging. Comparable studies have been published with surgical versus nonsurgical treatment and postoperative cast immobilisation versus early functional treatment. Although conservative treatment is popular in 1970s, surgical treatment seems to have been the method of choice in the late 1980s and the 1990s in athletes and young people; and in cases of delayed ruptures. Conservative management of Achilles tendon injury may be unrewarding except in low demand and very cooperative patients. The role of surgery in management of Achilles tendon rupture is discussed in detail with particular reference to the indications and the surgical procedures available. There is also no single, uniformly accepted surgical technique. Although early ruptures have been treated successfully with simple end-to-end suture, many authors have combined simple tendon suture with augmentation and plastic procedures of various types. Comparison of open versus percutaneous surgical methods also will be discussed in details. The complications of conservative treatment include mostly reruptures and residual lengthening of the tendon, which may result in significant calf muscle weakness.The major complaint against surgical treatment has been the high rate of complications. Most are minor wound complications, which delay improvement but do not influence the final outcome. Major complications are rare, but often difficult to treat with minor procedures.